Explaining how unexploded ordnance clearance enhances livelihoods in the Lao PDR. (February 2016) - Durham, Jo; Nanhthavong, Vong; Sychareun, Vanphanom
Highlights: Application of theory-based evaluation approach to mine action and clearance of unexploded ordnance program. Development of context-mechanism-outcome configurations to explain how mine action and clearance of unexploded ordnance programs work. Provides concrete suggestions for program planners and offers a more sophisticated program theory than the one seen in program documents. Abstract: Background: Following violent conflict, the continued presence of landmines and unexploded ordnance pose a barrier to rebuilding livelihoods. Mine action removes these explosive remnants of conflict to enable communities to safely return contaminated land to productive use. There is limited understanding, however, of how, why, in what context and in what respects mine action contributes to livelihoods. Yet, such information is required for effective resource allocation, checking underlying program assumptions, understanding benefits and potential harms. Methods: The evaluation was undertaken in the Lao People's Democratic Republic. It used an interpretive case study design and applied the principles of realist evaluation. Program staff and local government authorities were interviewed ( N = 37) and program beneficiaries. In total, 38 individual interviews with program beneficiaries were conducted and eighteen focus group interviews (9 with males, 9 with females), each with 6–9 participants. Results: The evaluation identified two main mechanisms through which the program 'worked': (1) communication pre- and post-clearance and (2) the delivery of the product (cleared land). Conclusion: The realist approach helped to refine the program theory, highlighted the role of self- and task-efficacy and community communication, assisted in identifying contextual factors that influence outcomes and suggested a revision of expected outcomes.